Avaliação da capacidade funcional de sobreviventes de Covid-19 no primeiro trimestre após alta hospitalar - FERREIRA, Eder Gabriel Soares (2021)
Introduction: Severe coronavirus 2 infection (SARS-CoV-2) and consequent coronavirus 2019 disease (COVID-19) has spread throughout the world, with extensive human, economic and health consequences. The proportion of patients with COVID-19-related functional disability has developed rapidly, and an immediate response is crucial to reduce disability and help restore and optimize functionality. Objective: To assess the functional capacity of COVID-19 survivors in the first trimester after hospital discharge. Methodology: This is a cross-sectional, analytical and descriptive study that was carried out at the Pulmonary Rehabilitation Outpatient Clinic of the João de Barros Barreto University Hospital. Surviving patients of COVID-19 were approached by telephone and invited to participate in the research. Those who accepted were submitted to functional capacity assessment through the application of the 6MWT’ up to three months after hospital discharge. Results: It was observed that 64% of the sample covered a value below 80% of the predicted in the 6MWT, with greater reduction values in non-practitioners of physical activity. Conclusion: We conclude that patients who had COVID-19 and were hospitalized and who do not practice physical activities prior to hospitalization have a reduction in functional capacity.